La noción de shareholder value y la teoría de los stakeholders: visión contemporánea del concepto de interés social desde una perspectiva de creación de valor. (2012)
By the present article; an exposition is made of what some label as the modern approaches to the concept of social interest : The theories of the shareholder value and of the stakeholders ; which are a contribution of the American doctrine to the problem posed by the management of the corporations of our time. A study is offered here of their antecedents; conception; evolution and relation to the listed corporation to determine the consequences of applying one or another in the management of the great society of capitals.